Improved Efficiency of Dye‐Sensitized Solar Cells Based on a Single Layer Deposition of Skein‐Like TiO2 Nanotubes. Issue 9 (28th June 2014) - Mojaddami, Majdoddin; Mohammadi, Mohammad Reza; Madaah Hosseini, Hamid Reza; Zhou, X.‐D.
<x xml:space="preserve">Abstract</x> We present a new TiO2 morphology, featuring high surface area and open structure, synthesized by a two‐step chemical route for the manufacture of dye‐sensitized solar cells (DSSCs). This construct is sets of intertwined one‐dimensional (1D) nanostructures (i.e., nanotubes), so‐called skein‐like nanotubes (NTs). Such morphology is produced by a combination of TiC oxidation and hydrothermal processes. The mesoporous TiO2 nanoparticles, as the product of TiC oxidation operation, is used as the precursor of hydrothermal process to grow the skein‐like NTs. The effect of processing parameters of TiC oxidation and hydrothermal processes is studied. The skein‐like morphology enables to eliminate the conventional three or fourfold layer deposition process by a single layer deposition of TiO2 NTs. The novel TiO2 morphology enhances photon capture of fabricated DSSC by exerting a triple function mechanism including improvement of light scattering, dye sensitization, and electron transport. The presented strategy demonstrates the feasibility of the new concept for improvement of cell efficiency by effective light management.